معايير للتحكم والوصول في النظم الخطية المتقطعة - عثمان محمود (Latakia University Journal -Basic Sciences Series, 2018)
في هذا البحث تم عرض بعض التعاريف والنظريات المشهورة في خواص قابلية التحكم والوصول للأنظمة الخطية المتقطعة ذات المعاملات الثابتة والتي تكتب على النحو التالي: X(t+1)=AX (t)+Bu(t+1) <!–?mso-application progid="Word.Document"?–> 12XT"> X(T)= X(0)=Xo 1 <!–?mso-application progid="Word.Document"?–> 12â‰¤"> |u(t)| وتم التوصل إلى ما يلي: 1- تحويل نظام التحكم إلى مسائل البرمجة الخطية. 2- إيجاد سلسلة من النتائج الجديدة في خواص قابلية التحكم والوصول لبعض الأنظمة الخطية المتقطعة. 3-وضع خوارزمية جديدة لإيجاد أقل عدد من الخطوات والتي نتمكن بها من نقل النظام من الحالة الابتدائية إلى الحالة النهائية ثم استنتاج متجهة التحكم. 4-وضع مثال يوضح صحة الخوارزمية السابقة. In this research many definitions and theories have been manifested regarding the specifications of controllability and accessibility in optimal control for discrete system of the type: X(t+1)=AX(t)+Bu(t+1) X(0)=Xo , |u(t)| 1 The following results have been reached : 1 - Transforming control system to the problem of linear programming. 2- Finding a series of new results of controllability and accessibility for optimal control discrete system. 3- Putting out a new algorithm to find the minimum number of steps that can enable us to move the state system from the primary stage into the final one. 4- Giving an example which shows the truthfulness of the previous algorithm .